From Anxiety to Engagement: Transforming an English for Specific Purposes Classroom Through Digital Storytelling - Lin, Shu-wen; Bollen, David Hugh (Universitas Syiah Kuala, 2025)
This mixed-methods study investigated the impact of integrating digital storytelling into an English for Specific Purposes (ESP) course for second-year undergraduate Landscape Architecture students at a Taiwanese university. The intervention aimed to mitigate speaking anxiety among these students and enhance their ESP learning. A modified version of the Foreign Language Speaking Anxiety Scale was used to quantitatively measure changes in students anxiety levels before and after the intervention. Qualitative data were collected through open-ended survey questions to explore students perceptions and experiences with digital storytelling. The quantitative results revealed a statistically significant decrease in students self-reported speaking anxiety levels after the intervention, particularly in relation to unprepared group interactions and conveying important information orally. Qualitative findings illuminated the mechanisms behind this reduction, emphasizing the positive impact of the iterative and collaborative nature of digital storytelling on language development, self-expression, and peer learning. Students reported increased engagement, enjoyment, and confidence in their speaking abilities. The study also identified challenges related to technical skills, language proficiency, and content integration, offering recommendations for addressing these issues in future implementations and research. This paper underscores the potential of digital storytelling as an effective pedagogical strategy in ESP courses, providing valuable insights into its educational benefits and practical challenges.This mixed-methods study investigated the impact of integrating digital storytelling into an English for Specific Purposes (ESP) course for second-year undergraduate Landscape Architecture students at a Taiwanese university. The intervention aimed to mitigate speaking anxiety among these students and enhance their ESP learning. A modified version of the Foreign Language Speaking Anxiety Scale was used to quantitatively measure changes in students anxiety levels before and after the intervention. Qualitative data were collected through open-ended survey questions to explore students perceptions and experiences with digital storytelling. The quantitative results revealed a statistically significant decrease in students self-reported speaking anxiety levels after the intervention, particularly in relation to unprepared group interactions and conveying important information orally. Qualitative findings illuminated the mechanisms behind this reduction, emphasizing the positive impact of the iterative and collaborative nature of digital storytelling on language development, self-expression, and peer learning. Students reported increased engagement, enjoyment, and confidence in their speaking abilities. The study also identified challenges related to technical skills, language proficiency, and content integration, offering recommendations for addressing these issues in future implementations and research. This paper underscores the potential of digital storytelling as an effective pedagogical strategy in ESP courses, providing valuable insights into its educational benefits and practical challenges.